UNLOCKING YOUTHS MANAGEMENT COMPETENCE IN REARING OF RABBITS FOR SELF-RELIANCE IN NSUKKA SENATORIAL ZONE OF ENUGU STATE, NIGERIA - EKELE, Garba Emmanuel; SHUAIB, Suleiman Bature (Ilorin Journal of Education, 2023)
Unemployment among the able youths has been recognized among social menace in Nigeria with Enugu State inclusive and rabbit production has been identified as a viable weapon to address this problem. This study, therefore, identified management competence required by youths in rabbits rearing for self -reliance in Nsukka Senatorial Zone of Enugu State. Three research questions and three hypotheses were formulated to guide the study. The population for the study was 297. The sample size for the study was 103 selected through purposive sampling procedure. A 30-item questionnaire titled: ‘Youth Management Competence for Rabbit Rearing Questionnaire’ (YMCRRQ) was used for data collection. The instrument was face validated by three experts. Cronbach Alpha Method was used to determine the internal consistency of the questionnaire items which yielded a coefficient of 0.79. Mean was used to analyze the data and t-test statistics was used to test the null hypotheses at 0.05 level of significance. It was found out that the youths required all the management competencies in feeding, management and housing of rabbits. It was recommended that all the managerial competencies be used to train youths as a package for sustainable self –reliance in Nsukka Senatorial Zone of Enugu State.